Pengaruh Manajemen SDM dan Kompensasi terhadap Kinerja Karyawan yang Dimediasi oleh Kompetensi di Mitra10 Semarang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of human resource management, compensation, and competency levels on employee performance at Mitra10 Semarang. The research method used a quantitative method with an explanatory research approach, involving 53 samples determined through simple random sampling. Data collection techniques in this study used a Likert scale questionnaire, which was then analyzed using SmartPLS 4. The results of the analysis indicate that HRM has a positive and significant influence on employee performance. Compensation also has a positive and significant impact on performance. Concurrently, HRM and compensation positively and significantly influence employee competence. These competencies also have a significant positive contribution to employee performance. These findings confirm that improving employee performance requires effective human resource management, a fair compensation system, and continuous competency development. Practical recommendations include evaluating the compensation system, improving training programs, and creating a conducive work environment to encourage productivity